The cardiovascular system : development, plasticity and physiological responses - Gamperl, A. Kurt (Anthony Kurt); Gillis, Todd E.; Farrell, Anthony Peter, 1952-; Brauner, Colin J. (Fish physiology ;, 2017)
The Cardiovascular System: Phenotypic and Physiological Responses, Volume 37, part of a two-volume set, provides comprehensive coverage of the current state of knowledge in this very active and growing field of research, also highlighting the tremendous diversity in cardiovascular morphology and function among the various fish taxa and the anatomical and physiological plasticity shown by this system when faced with various abiotic and biotic challenges. Specific chapters in this updated book include Research Technologies/Methodology for Studying Fish Cardiovascular Function, Cardiovascular Development in Embryonic and Larval Fishes, Cardiovascular Responses to Limiting Oxygen Levels, and Temperature and the Cardiovascular System. The book's chapters integrate molecular and cellular data with the growing body of knowledge on heart and in vivo cardiovascular function, and as a result, provide insights into some of the most interesting, and important, questions that still need to be answered in this field. Presents a comprehensive overview of cardiovascular structure and function in fishProvides a valuable resource for researchers in fish physiology and audiences within the fields of comparative morphology and histology, aquaculture and ecophysiologyHighlights the tremendous diversity in cardiovascular morphology and function among the various fish taxa